Feeding steam-flaked diets with and without dry-rolled corn and dried distillers grains results in similar feedlot performance - Black, P.L.; Parsons, G.L.; Shelor, M.K.; Karges, K.K.; Gibson, M.L.; Reinhardt, Christopher D.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Increased ethanol production in the United States has increased availability of by-products, giving producers an alternative to cereal grains. The by-product we evaluated was dried corn distillers grains with solubles. Research has been conducted at Kansas State University to evaluate the quantity of distillers grains that can be added to a finishing diet without negatively affecting feedlot performance or carcass value. Feeding cattle distillers grains is an important option for feedlots to consider. The second issue that has arisen is the energy costs associated with processing grains. In Kansas, two of the more common methods for processing grains are steam flaking and dry rolling. Previous research has shown that the nutritive value of distillers grains can be influenced by grain processing method. This experiment was designed to evaluate feedlot performance and carcass merit in heifers fed flaked-corn diets with added dry-rolled corn and/or dried corn distillers grains.
Keywords: Beef; Cattle; Distillers grains